Optimalisasi Pemberdayaan Pelaku UMKM Melalui Edukasi Literasi Keuangan - Effendi, Bahtiar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) IAIN Manado, 2022)
The article provides financial management learning assistance to improve the financial management capabilities of Small and Medium Enterprises (UMKM). This research uses a descriptive method. Three activities in conducting this research; introduction, mentoring and evaluation. As for this research method includes: the preparation stage which consists of observation, interviews with village heads, delivery of materials, and material counseling, implementation stage consists of the implementation of seminar activities initiated by the approach and assistance to business actors, the evaluation stage of the evaluation of activities that have been carried out have been done. The results of the activity showed that the ability of the learning mentoring participants increased after this community service activity was held.